Modifying Cement Hydration with NS@PCE Core-Shell Nanoparticles - Yue Gu; Qianping Ran; Wei She; Jiaping Liu (Advances in Materials Science and Engineering)
It is generally accepted that fine particles could accelerate cement hydration process, or, more specifically, this accelerating effect can be attributed to additional surface area introduced by fine particles. In addition to this view, the surface state of fine particles is also an important factor, especially for nanoparticles. In the previous study, a series of nano-SiO2-polycarboxylate superplasticizer core-shell nanoparticles (NS@PCE) were synthesized, which have a similar particle size distribution but different surface properties. In this study, the impact of NS@PCE on cement hydration was investigated by heat flow calorimetry, mechanical property measurement, XRD, and SEM. Results show that, among a series of NS@PCE, NS@PCE-2 with a moderate shell-core ratio appeared to be more effective in accelerating cement hydration. As dosage increases, the efficiency of NS@PCE-2 would reach a plateau which is quantified by various characteristic values. Compressive strength results indicate that strength has a linear correlation with cumulative heat release. A hypothesis was proposed to explain the modification effect of NS@PCE, which highlights a balance between initial dispersion and pozzolanic reactivity. This paper provides a new understanding for the surface modification of supplementary cementitious materials and their application and also sheds a new light on nano-SiO2 for optimizing cement-based materials.